The reality of the teaching strategies used by teachers of intellectual disability in the Asir region - Alshehri, Amer Abdullah Amer; Abu Alghaith, Khaled Muhammed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the teaching strategies used by intellectual disability teachers in Asir region, and this study relied on the descriptive curriculum, and the sample of the study consisted of the teachers of intellectual disability in the area of Assir (89) teachers and teachers where the sample was taken in the style of a simple random sample, and the questionnaire took a tool for it in collecting data and information. Highlights of the study include:- The study members were found to agree "sometimes" with the teaching strategies used by intellectual disability teachers in the Assir region with an average calculation (2.32), with average approvals for trends ranging from (2.00 to 2.65) , which are in the second and third category of scale categories that refer (sometimes-always) to the study tool There are differences between the answers of the study sample members at the centre of the teaching strategies used by intellectual disability teachers in the Assir region in terms of sex for females. There are no differences between the answers of the study sample members on the focus of the teaching strategies used by intellectual disability teachers in the Asir region in terms of obtaining training courses on teaching methods and strategies. There are differences between the answers of the study sample members at the center of the teaching strategies used by intellectual disability teachers in The Assir region in terms of the number of years of teaching experience for the benefit of their teaching experience less than 5 years. The study recommended the need to train teachers of students with intellectual disabilities to diversify the use of appropriate teaching strategies in teaching for students with intellectual disabilities, to hold training courses and workshops to train teachers in the use of different teaching strategies, use appropriate software in teaching strategies to students with intellectual disabilities, enroll teachers of education for effective training courses in strategies to teach students with intellectual disabilities, work to provide material resources in special education schools to apply Modern teaching strategies.